Pengaruh Musik Gamelan Terhadap Peningkatan Pemahaman Bacaan Pada Pelajar SMP Kanisius Kalasan Kelas 1 - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
This research aims at finding whether gamelan music, with approximate 60 beats per minute and has no lyrics, has influence to level of reading comprehension.12 -14 years-old Junior High School's students are the subject of this reasearch. Subjects came from the same school and also have the same teacher for their Bahasa Indonesia lesson, in order to have a homogenious ability of their reading comprehension. A questionaire was conducted to know subjects' kinds of music that subjects hear in their daily study and those kinds of music are categorized into 3 category, (1) without music, (2) popular music, and (3) gamelan music.Pretest result shows that level of reading comprehension between experiment group and control group is the same. Post-test indicated that experiment group's level of reading comprehension is higher than control group. In experiment group, subjects with pop music as their study preference is higher than gamelan music and no music as their study preference.